Cloning and Expression of Nano Body Gene against Enterotoxin B of Staphylococcus Aureus - Zahra Tavassoli; Hamideh Rouhani Nejad; Jalil Fallah Mehrabadi (Fasa University of Medical Sciences, 2016)
Background & Objectives: Staphylococcus aureus bacteria causes many different diseases by secretion of various enterotoxins. Therefore, it is necessary to develop ways that facilitate the detection of enterotoxins. Nowadays, immunochemical methods which are based on monoclonal antibody technology are used. The heavy chain antibodies that are called VHH or Nano body were found in blood serum of the Camelidae family. The unique properties of this antibody such as their binding to small molecules like toxins make them attractive candidates for the development of immunodiagnostic tests. The present study was done to achieve a VHH molecules against Staphylococcus enterotoxin B. Materials & Methods: Freighting phage library for isolate private Nano bodies against enterotoxin B was done in previous works. Next, pCANTAB 5E vector that consists VHH, extracted from E.coli bacteria strain xl1blue, and after doing PCR process with relative primers, sub cloning in pET21a(+) as an expression vector with cut sites NdeI and XhoI was done. Transformation in E.coli bacteria strain BL21(DE3) was done. Then, the cells effected with IPTG and producing time, and other terms were optimized. Finally, the expression of the protein with SDS-PAGE and western blot techniques was evaluated. Result: For proving cloning of nano body gene in pET21a (+) vector, nucleotide sequence of gene was analyzed, and transforming to E.coli bacteria strain BL21(DE3) was successful. After inspiration, active protein in cell was seen by SDS-PAGE technique and proved by western blot. Conclusion: cloning, sub cloning, and nonabody expression were surveyed in this research. Production of this protein can help to develop new therapeutic methods and produce vaccine against enterotoxin B of Staphylococcus aureus